Fibroblast Growth Factor 23 and Incident Cardiovascular Disease and Mortality in Middle‐Aged Adults - Shejuti Paul; Mandy Wong; Ehimare Akhabue; Rupal C. Mehta; Holly Kramer; Tamara Isakova; Mercedes R. Carnethon; Myles Wolf; Orlando M. Gutiérrez (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Higher circulating fibroblast growth factor 23 (FGF23) associates with greater risk of cardiovascular disease (CVD) and mortality in older adults. The association of FGF23 with cardiovascular outcomes in younger populations has been incompletely explored. Methods and Results We measured C‐terminal FGF23 (cFGF23) and intact FGF23 (iFGF23) in 3151 middle‐aged adults (mean age, 45±4) who participated in the year 20 examination of the CARDIA (Coronary Artery Risk Development in Young Adults) study. We used separate Cox proportional hazards models to examine the associations of cFGF23 and iFGF23 with incident CVD and mortality, adjusting models sequentially for sociodemographic, clinical, and laboratory factors. A total of 157 incident CVD events and 135 deaths occurred over a median 7.6 years of follow‐up (interquartile range, 4.1–9.9). In fully adjusted models, there were no statistically significant associations of FGF23 with incident CVD events (hazard ratio per doubling of cFGF23: 1.14, 95%CI 0.97,1.34; iFGF23: 0.76, 95%CI 0.57,1.02) or all‐cause mortality (hazard ratio per doubling of cFGF23, 1.17; 95% CI, 1.00–1.38; iFGF23, 0.86; 95% CI, 0.64–1.17). In analyses stratified by CVD subtypes, higher cFGF23 was associated with greater risk of heart failure hospitalization (hazard ratio per doubling of cFGF23, 1.52; 95% CI, 1.18–1.96) but not coronary heart disease or stroke, whereas iFGF23 was not associated with CVD subtypes in any model. Conclusions In middle‐aged adults with few comorbidities, higher cFGF23 and iFGF23 were not independently associated with greater risk of CVD events or death. Higher cFGF23 was independently associated with greater risk of heart failure hospitalization.